The Role of Teaching Materials / Textbooks on Visual Perception and Visual Interpretation - Miroslav Huzjak (European Scientific Journal, ESJ, 2017)
Perception depends on the mental interpretation. Our mind contains categories through which it interprets and gives sense to what was perceived. Categories are acquired through learning, and textbooks play an important role in the process of learning. Images of cubes in textbooks, particularly mathematics textbooks, are in contradiction with the central perspective, i.e. with the way in which we visually perceive them. Such images of cubes do not match mathematical axonometric projections either. Images of cubes in textbooks present the front side as a square with parallel sides, one lateral side, and the top side. Such a presentation is optically incorrect and stereotypical, creating a category that blights the visual perception and drawing interpretation of a cube in a space. In our empirical research, participants were presented with a cube above their horizon making it impossible to see its top side. While drawing the cube, a large number of participants had a blighted perception and interpretation. They drew the cube in a stereotypical manner, as a square with the top facet, which could actually not be seen. What is more, because of the perspective, the front side is not seen as a square anymore. The drawings were evaluated according to their success in presentation that was afterwards compared with the achievement in the written test of perception. The research was carried out in two countries, Croatia and Slovenia. The sample consisted of 217 participants in the fourth, sixth and eighth grades of primary school and third and fifth year of university.